Awareness and Knowledge of Saudi Community about Cardiac Complications Resulting from Hyperthyroidism - Alghamdi, Khalid; Almalki, Rinad; Almalki, Khaled; Alzahrani, Waad; Malyani, Rana; Samaran, Yomna; Alzahrani, Khames (International Journal of Innovative Research in Medical Science, 2021)
Background: The misconceptions about thyroid disorders and the associated complications in many counties are a considerable concern. Thyroid disorders are amongst worldwide common endocrine disorders. Based on the World Health Organization, more than 190 million individuals have iodine deficiency disorders. Most importantly, hyperthyroidism alters the cardiovascular (CV) hemodynamic. Methods: A cross-sectional observational survey study that was carried out in Saudi Arabia using an online self-prepared questionnaire including socio-demographic data, disease manifestations, diagnosis, family history, and question regarding hyperthyroidism and CV complications. That was distributed, via a link to Google form, to the general public. Only completed surveys were included in the analysis. Data were represented in the form of frequencies (number of responders) and valid percentages for categorical variables. ANOVA test was utilized to compare means between different subgroups. All P values < 0.05 were considered statistically significant. Result: A total of 641 participants took part in this study and achieved a mean score of 4.7 (SD 1.5) of the total score obtainable regarding hyperthyroidism. Out of them, 51.3% did not perform thyroid hormones investigation or having family history of thyroid disorders (46.8%). Adequate knowledge was seen regarding the occurring of heart diseases as a complication of hyperthyroidism (80.5%) and preventing CV disease by treating hyperthyroidism (88.6%). 68.8% did not know which heart complications result from hyperthyroidism. There was a statistically significant relationship between the level of knowledge and age (p<0.001), sex (p=0.004), undergoing previous thyroid investigations (p=0.003) and being diagnosed with previous thyroid disease (p<0.001). Nationality and education had no significant effect on the knowledge level of the participants. Conclusion: In this study, the overall level of Knowledge about thyroid disorders in the community was limited. Better knowledge was found about CV complications of hyperthyroidism. Educational programs will have a positive influence of awareness on thyroid troubles and will help in early diagnosis of these disorders and prevent CV diseases.